Photosensitive nanoparticle preparation method, photoresist solution and two-photon pattern

By preparing photosensitive nanoparticles in two-photon polymeric materials, the problems of light scattering, heat accumulation, and low solubility of inorganic fillers in two-photon polymeric materials are solved, and high-quality two-photon patterning is achieved.

CN119322428APending Publication Date: 2025-01-17YONGJIANG LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411655003.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

In two-photon polymeric materials, there are problems of light scattering, heat accumulation and solubility when introducing inorganic fillers, resulting in damage to printing resolution and quality.

Method used

A method for preparing photosensitive nanoparticles is used to generate metal oxygen clusters through the reaction of a metal salt solution and an unsaturated carboxylic acid ligand, and a photoinitiating ligand is introduced through an acid ligand exchange reaction to form photosensitive small-sized nanoparticles. .

Benefits of technology

The prepared photosensitive nanoparticles have small particle size, good dispersion and photosensitivity. They can effectively solve the problems of insoluble fillers, light scattering and heat accumulation, and improve the pattern quality of two-photon patterning.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119322428A_ABST
    Figure CN119322428A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of photosensitive nanoparticles, a photoresist solution and a two-photon pattern. A metal oxygen cluster with a metal core and an organic shell containing a carboxylic acid group is subjected to an acid ligand exchange reaction, so that an acid ligand with a photo-initiation effect is introduced into the metal oxygen cluster, the photosensitive nano-particles are obtained, the particle size is small, the photosensitive nano-particles have photosensitivity, the miscibility with a photoresist matrix is good, and the extremely small particle size can still be kept after mixing; therefore, the two-photon photoresist can be used as a filler to form a photoresist solution to obtain a high-quality two-photon pattern.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of photosensitive materials and photolithography technology, and in particular to a method for preparing photosensitive nanoparticles, a photoresist solution and a two-photon pattern. Background Art

[0002] Adding inorganic fillers to organic resins to form composite materials is a common method to improve mechanical properties in the field of 3D macro printing. For example, graphene oxide fillers can significantly improve the mechanical strength of commercial resins. If inorganic fillers are introduced into two-photon polymerization materials, there are special requirements because inorganic fillers may encounter some potential obstacles when interacting with lasers. These obstacles include the large size and agglomeration of fillers, which may cause serious light scattering and heat accumulation problems, thereby destroying the resolution and quality of printing.

[0003] In addition, in the field of two-photon polymerization materials, there are still problems such as the lack of simple functionalization and customization of fillers, the low solubility of fillers in viscous organic monomers, and the possibility that fillers may interact with free radicals and quench the polymerization reaction. Summary of the invention

[0004] In view of the above-mentioned technical status, the present invention provides a method for preparing photosensitive nanoparticles. The method is simple and easy, and the prepared nanoparticles have a small particle size, good dispersibility in the photoresist matrix, and photosensitivity. They can be used as fillers in the photoresist matrix to constitute a photoresist solution for two-photon patterning to obtain 2D or 3D patterns.

[0005] That is, the technical solution of the present invention is: a method for preparing photosensitive nanoparticles, comprising the following steps:

[0006] (1) Preparation of metal oxide clusters

[0007] A metal salt solution is mixed with an unsaturated carboxylic acid ligand, heated for reaction, and then cooled to precipitate crystals to obtain a metal oxygen cluster having a metal core and an organic shell containing a carboxylic acid group;

[0008] (2) Introduction of photoinitiator ligands

[0009] The metal oxo cluster obtained in step (1) is dissolved in a second solvent to obtain a metal oxo cluster solution, and then a photoinitiator carboxylic acid ligand is added and stirred in the dark, and the photoinitiator ligand is introduced into the organic shell of the metal oxo cluster through an acid ligand exchange reaction to form photosensitive nanoparticles.

[0010] The metal salt solution is composed of a metal salt and a first solvent, wherein the metal salt is not limited and can be selected from one or more of zirconium alcoholate, zirconium carboxylate, zirconium sulfonate, zirconium sulfate, zirconium halide and the like.

[0011] The first solvent is not limited and can be selected from one or more of alcohols, esters, hydrocarbons, etc.

[0012] The unsaturated carboxylic acid ligand comprises a carboxylic acid group and can react with a metal salt to obtain an organic shell having a metal core and consisting of the unsaturated carboxylic acid ligand.

[0013] The unsaturated carboxylic acid ligand may be selected from one or more of acrylic acid, methacrylic acid, 2-propyl acrylic acid, 2,3-dimethylacrylic acid, vinylbenzoic acid, trifluoromethylacrylic acid and the like.

[0014] The heating temperature is not limited and is determined according to the actual reaction conditions of different metals in precipitating metal oxygen clusters, for example, 90°C-120°C.

[0015] In the step (1), the process of cooling and precipitating crystals is not limited. Preferably, a step-by-step cooling method is used and maintained for a certain period of time to cool and precipitate crystals. For example, the temperature is first cooled to 60°C-80°C and maintained for 1h-10h, then cooled to 40°C-60°C and maintained for 1h-10h, and finally cooled to room temperature and allowed to stand for 1h-20h.

[0016] The particle size of the metal oxygen clusters is in the range of 0.5 nm to 5 nm, and is particularly concentrated in the range of 1 nm to 2 nm.

[0017] In the step (2), the mass ratio of the photo-initiated carboxylic acid ligand to the metal oxygen cluster is not limited and can be selected from (0.1-1):1.

[0018] The second solvent is not limited and can be selected from one or more of propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, toluene, acetone, chloroform and the like.

[0019] The photoinitiated carboxylic acid ligand is not limited and can be selected from one or more of benzophenone carboxylic acid, thioxanthone carboxylic acid, coumarin carboxylic acid, etc. Among them, benzophenone carboxylic acid can be selected from one or more of 4-benzoylbenzoic acid, o-benzoylbenzoic acid, 2'-aminobenzophenone-2-carboxylic acid, 3',4'-dimethylbenzophenone-2-carboxylic acid; thioxanthone carboxylic acid can be selected from one or more of 9-oxo-9H-thioxanthene-4-carboxylic acid, 9-oxo-9h-thioxanthene-2-carboxylic acid, 9-oxo-9h-thioxanthene-1-carboxylic acid, etc.; coumarin carboxylic acid can be selected from one or more of 7-(diethylamino)coumarin-3-carboxylic acid, coumarin-3-carboxylic acid, 7-hydroxycoumarin-3-carboxylic acid, etc.

[0020] After step (2), a solution containing photosensitive nanoparticles is obtained.

[0021] The particle size of the photosensitive particles is in the range of 0.5 nm to 5 nm, and is particularly concentrated in the range of 1 nm to 2 nm.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The present invention utilizes a metal oxygen cluster having an atomically precise metal core and an organic shell containing a carboxylic acid group, and introduces an acid ligand having a photoinitiating effect into the metal oxygen cluster through an acid ligand exchange reaction to obtain photosensitive nanoparticles. The method is simple and easy to implement, and the obtained photosensitive nanoparticles have a small particle size and are photosensitivity, for example, there are absorption peaks at 258nm and 390nm, which can be used for two-photon absorption reaction to achieve patterning.

[0024] (2) The photosensitive nanoparticles prepared by the preparation method of the present invention have good miscibility with the photoresist matrix and can still maintain an extremely small particle size after mixing, and can be used as photoresist fillers in two-photon patterning. On the one hand, it solves the problem of the filler being difficult to dissolve in the photoresist matrix in the prior art, and realizes efficient doping of the filler. On the other hand, it solves the problem of large filler particles causing particle agglomeration, light scattering and heat accumulation in the two-photon patterning technology, which leads to damage to the pattern quality.

[0025] That is, the present invention also provides a photoresist solution, comprising an organic resin and photosensitive nanoparticles obtained by the preparation method of the present invention. The 2D or 3D pattern obtained by two-photon manufacturing using the photoresist solution has good structural quality.

[0026] After step (2) of the preparation method of the present invention, a solution containing photosensitive nanoparticles is obtained. As an implementation method, the photoresist solution can directly utilize the solution containing photosensitive nanoparticles, and organic resin is added thereto and mixed evenly.

[0027] (3) The present invention can realize the functionalization of the photoresist by designing the interaction force between the photosensitive ligand and the organic resin. For example, when the photosensitive ligand contains an amino group, it forms a hydrogen bond with the hydroxyl group of the organic resin, which can improve the mechanical properties of the printed structure.

[0028] The organic resin is not limited and may be selected from one or more of pentaerythritol tetraacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, and polydipentaerythritol pentaacrylate.

[0029] In the photoresist solution, the mass ratio of the organic resin to the photosensitive nanoparticles can be selected from (1-9):1.

[0030] As an implementation method, the preparation method of the photoresist solution is as follows:

[0031] An organic resin monomer is added to the solution containing the photosensitive nanoparticles obtained by the preparation method of the present invention, and the mixture is evenly mixed and then filtered to obtain a clear photoresist solution.

[0032] As an implementation method, the method of performing two-photon patterning using the photoresist solution is as follows:

[0033] The photoresist solution is drop-cast or spin-coated on a substrate, and after drying the solvent, back-side patterning printing is performed. After completion, the substrate is taken out and immersed in a developer for development, and then dried with an inert gas to obtain a 2D or 3D pattern.

[0034] The substrate is not limited and can be selected from polished silicon wafers, quartz wafers, sapphire wafers, and the like.

[0035] The photoresist solution can be coated or spin-coated on a substrate, and the coating rate is not limited and can be selected from 1000 rpm / min-4000 rpm / min.

[0036] The drying temperature is not limited and can be selected from 60°C to 110°C.

[0037] The developer is not limited and can be selected from one or more of isopropyl alcohol, toluene, o-xylene, 4-methyl-2-pentanol, propylene glycol monomethyl ether acetate, ethyl acetate and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 It is a particle size distribution diagram of the Zr-MOC powder obtained in Example 1, the Zr-BPA obtained in Example 2, and the Zr-ACA obtained in Example 3 tested by a dynamic light scattering instrument.

[0039] Figure 2 These are the ultraviolet absorption curves of the Zr-MOC powder obtained in Example 1, the Zr-BPA obtained in Example 2, and the Zr-ACA obtained in Example 3 obtained by testing with an ultraviolet spectrometer.

[0040] Figure 3 It is a schematic diagram of the relative positions of the substrate and the stage during 3D patterning.

[0041] Figure 4 These are the 2D and 3D patterns of the photoresist solution of Example 4-1 under two-photon exposure.

[0042] Figure 5 These are the 2D and 3D patterns of the photoresist solution of Example 4-2 under two-photon exposure.

[0043] Figure 6 These are the 2D and 3D patterns of the photoresist solution of Example 4-3 under two-photon exposure.

[0044] Figure 7 It is the 3D pattern of the photoresist of comparative example 5-2 under two-photon exposure.

[0045] Figure 8The stress-strain curves of the 3D structures printed by Example 4-2, Example 4-3 and Comparative Example 5-2 were obtained through in-situ mechanical testing. DETAILED DESCRIPTION

[0046] The present invention is further described in detail below in conjunction with embodiments. It should be pointed out that the embodiments described below are intended to facilitate the understanding of the present invention, and non-essential improvements and adjustments made to the present invention by those skilled in the art based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.

[0047] The words “include”, “including” and the like used in the present invention should be interpreted as including rather than being exclusive or exhaustive; that is, the meaning is “including but not limited to”.

[0048] The expressions “first”, “second”, etc. used in the present invention may modify various constituent elements regardless of the order and / or importance, and are only used to distinguish one constituent element from another constituent element, but do not limit the corresponding constituent elements.

[0049] Embodiment 1:

[0050] Zirconium n-propoxide and n-propanol are mixed to obtain a zirconium n-propoxide-n-propanol solution, wherein the mass percentage concentration of n-propanol is 70%; 10 g of the zirconium n-propoxide-n-propanol solution is mixed with 10 g of methacrylic acid, stirred evenly, and placed in a 100° C. oil bath for 18 hours, then cooled to 60° C. and maintained for 6 hours, then cooled to 40° C. and maintained for 6 hours, and finally allowed to stand at room temperature for two days to obtain precipitated crystals, which are filtered and vacuum dried to obtain a white powder, i.e., zirconium-metal oxygen cluster (Zr-MOC).

[0051] Embodiment 2:

[0052] Take 1 g of the Zr-MOC powder and 0.13 g of 4-benzoylbenzoic acid in Example 1, dissolve them in a mixed solvent of 0.9 g of chloroform and 8.1 g of propylene glycol monomethyl ether acetate, and stir in the dark for 24 h after ultrasonication for 15 minutes to form zirconium-4-Benzoylbenzoic acid (Zr-BPA).

[0053] Embodiment 3:

[0054] Take 1 g of the Zr-MOC powder in Example 1 and 0.14 g of 2'-aminobenzophenone-2-carboxylic acid, dissolve them in a mixed solvent of 9 g of chloroform and 8.1 g of propylene glycol monomethyl ether acetate, and stir in the dark for 24 h after ultrasonication for 15 minutes to form zirconium-2'-aminobenzophenone-2-carboxylic acid (Zirconium-2'-Aminobenzophenone-2-Carboxylic Acid, denoted as Zr-ACA).

[0055] The particle size distribution of the Zr-MOC powder obtained in Example 1, the Zr-BPA obtained in Example 2, and the Zr-ACA obtained in Example 3 obtained by dynamic light scattering is as follows: Figure 1 As shown, it can be seen that the particle size distribution of Zr-MOC powder is in the range of 0.7nm-5nm, especially concentrated in the range of 1nm-2nm. When photosensitive ligands are introduced into Zr-MOC powder to obtain Zr-BPA or Zr-ACA, the particle size and distribution are basically maintained.

[0056] The ultraviolet absorption curves of the Zr-MOC powder obtained in Example 1, the Zr-BPA obtained in Example 2, and the Zr-ACA obtained in Example 3 obtained by ultraviolet spectrometer testing are as follows: Figure 2 As shown, it can be seen that Zr-MOC powder has no absorption at 258 nm, and Zr-BPA and Zr-ACA obtained after introducing photosensitive ligands into Zr-MOC powder both have absorption at 258 nm.

[0057] Example 4-1:

[0058] 1 g of pentaerythritol triacrylate was added to the product obtained in Example 2 (the solution containing Zr-BPA) and stirred for 4 hours, and then used as a photoresist solution (referred to as Zr-BPA-PETA) for two-photon patterning, as follows:

[0059] The two-photon exposure system uses a 515nm laser. According to the principle of two-photon nonlinear absorption, the photoresist needs to absorb at 258nm to react and achieve patterning.

[0060] Patterning method: The photoresist solution is filtered and then drop-casted or spin-coated on the substrate. The relative position of the substrate and the stage is as follows: Figure 3 , there is photoresist solution under the substrate and mirror oil on the top to soak the lens; during patterning, the laser with a wavelength of 515nm will be focused on the plane where the photoresist contacts the substrate, and the stage moves upward with high precision according to the program to perform patterning in the photoresist in this step; after patterning, the substrate is taken out and completely immersed in propylene glycol monomethyl ether acetate for 5 minutes, and 2D and 3D patterns are obtained after drying with nitrogen.

[0061] The 2D and 3D patterns obtained in this embodiment are shown in the attached Figure 4 .

[0062] Example 4-2:

[0063] 1 g of pentaerythritol triacrylate was added to the product obtained in Example 3 (liquid containing Zr-ACA) and stirred for 4 h. The resulting solution was used as a photoresist solution (referred to as Zr-ACA-PETA) for two-photon patterning. The patterning method was the same as that in Example 4-1. The obtained 2D and 3D patterns are shown in the attached figure. Figure 5 .

[0064] Example 4-3:

[0065] 1 g of trimethylolpropane triacrylate (TMPTA) was added to the product obtained in Example 3 (liquid containing Zr-ACA) and stirred for 4 h. After that, two-photon patterning was performed as a photoresist solution (referred to as Zr-ACA-TMPTA). The patterning method was the same as that in Example 4-1. The obtained 2D and 3D patterns are shown in the attached figure. Figure 6 .

[0066] Comparative Example 5-1:

[0067] 1 g of the Zr-MOC powder obtained in Example 1 was dissolved in a mixed solvent of 0.9 g of chloroform and 8.1 g of propylene glycol monomethyl ether acetate, and then 1 g of pentaerythritol triacrylate was added and stirred for 4 hours. The mixture was used as a photoresist for two-photon patterning. The patterning method was the same as that in Example 4-1, and no pattern could be obtained.

[0068] Comparative Example 5-2:

[0069] 2 g of pentaerythritol triacrylate was dissolved in a mixed solvent of 0.9 g of chloroform and 8.1 g of propylene glycol monomethyl ether acetate, and 0.03 g of I3E photoinitiator was added. After mixing and stirring for 4 hours, a photoresist composition (referred to as (PETA)) was used for two-photon patterning. The obtained pattern was as follows: Figure 7 The I3E photoinitiator is composed of 2-isopropylthioxanthone, 2-benzyl-2-dimethylamino-1-(4-morpholinephenyl)butanone and 4-dimethylamino-ethyl benzoate in a mass ratio of 1:1:1.

[0070] Comparative Example 5-2, the 3D structures printed in Example 4-2 and Example 4-3 were subjected to in-situ mechanical testing to obtain stress-strain curves as shown in Figure 8 As shown, it can be seen that:

[0071] (1) The mechanical properties of the 3D micro-column structures printed by Examples 4-2 and 4-3 are significantly higher than those of the 3D micro-column structure printed by Comparative Example 5-2;

[0072] (2) Compared with Example 4-3, the 3D microcolumn structure printed in Example 4-2 exhibits higher mechanical properties because PETA contains hydroxyl groups, which form hydrogen bonds with the amino groups in the photosensitive ligands, thereby improving the mechanical properties of the printed structure.

[0073] The above-described embodiments provide a detailed description of the technical solutions of the present invention. It should be understood that the above descriptions are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing photosensitive nanoparticles, characterized in that: The steps include: (1) mixing a metal salt solution with an unsaturated carboxylic acid ligand, heating for reaction, and then cooling to precipitate crystals to obtain a metal oxygen cluster having a metal core and an organic shell containing a carboxylic acid group; (2) dissolving the metal oxo cluster obtained in step (1) in a second solvent to obtain a metal oxo cluster solution, then adding a photoinitiator carboxylic acid ligand and stirring in the dark, and introducing the photoinitiator ligand into the organic shell of the metal oxo cluster through an acid ligand exchange reaction to form photosensitive nanoparticles.

2. The preparation method according to claim 1, characterized in that: The metal salt solution consists of a metal salt and a first solvent; Preferably, the metal salt is selected from one or more of zirconium alkoxide, zirconium carboxylate, zirconium sulfonate, zirconium sulfate and zirconium halide; Preferably, the first solvent is selected from one or more of alcohols, esters, and hydrocarbons; Preferably, the unsaturated carboxylic acid ligand is selected from one or more of acrylic acid, methacrylic acid, 2-propyl acrylic acid, 2,3-dimethylacrylic acid, vinylbenzoic acid, and trifluoromethylacrylic acid.

3. The preparation method according to claim 1, characterized in that: The particle size of the metal oxygen cluster is in the range of 0.5nm-5nm; Preferably, the particle size of the metal oxide cluster is in the range of 1 nm to 2 nm.

4. The preparation method according to claim 1, characterized in that: The photoinitiated carboxylic acid ligand is selected from one or more of benzophenone-type carboxylic acid, thioxanthone-type carboxylic acid, coumarin-type carboxylic acid, etc.; Preferably, the benzophenone-type carboxylic acid is selected from one or more of 4-benzoylbenzoic acid, o-benzoylbenzoic acid, 2'-aminobenzophenone-2-carboxylic acid, and 3',4'-dimethylbenzophenone-2-carboxylic acid; Preferably, the thioxanthone-type carboxylic acid is selected from one or more of 9-oxo-9H-thioxanthene-4-carboxylic acid, 9-oxo-9h-thioxanthene-2-carboxylic acid, 9-oxo-9h-thioxanthene-1-carboxylic acid, etc.; Preferably, the coumarin-type carboxylic acid is selected from one or more of 7-(diethylamino)coumarin-3-carboxylic acid, coumarin-3-carboxylic acid, 7-hydroxycoumarin-3-carboxylic acid and the like.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the photoinitiated carboxylic acid ligand to the metal oxygen cluster is (0.1-1): 1; Preferably, the second solvent is selected from one or more of propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, toluene, acetone and chloroform.

6. The preparation method according to claim 1, characterized in that: The particle size of the photosensitive nanoparticles is in the range of 0.5nm-5nm; Preferably, the particle size of the photosensitive nanoparticles is in the range of 1 nm-2 nm.

7. The photosensitive nanoparticles prepared by the preparation method according to any one of claims 1 to 6 are used as photoresist fillers in two-photon patterning.

8. A photoresist solution, characterized in that: The invention comprises an organic resin and the photosensitive nanoparticles according to any one of claims 1 to 6.

9. A photoresist solution as claimed in claim 8, characterized in that: The organic resin is selected from one or more of pentaerythritol tetraacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate and polydipentaerythritol pentaacrylate.

10. A two-photon pattern, characterized in that: The method is obtained by performing two-photon patterning using the photoresist solution described in claim 8 or 9.

11. A two-photon pattern as claimed in claim 10, characterized in that: The two-photon patterning method comprises: drop casting or spin coating the photoresist solution on a substrate, drying the solvent and performing back-side patterning printing, taking out the substrate and immersing it in a developer for development, and drying it with an inert gas to obtain a 2D or 3D pattern.